A critical study on the extent of the issues and challenges facing the pharmacy enforcement officers in the enforcement of counterfeit medicines in Malaysia, with special reference to the position in England and Wales / Mohd Khairul Azwan Wahab, Azlinda Abdul Samad - Azwan Wahab, Mohd Khairul; Abdul Samad, Azlinda (2009)
Counterfeit medicine is a threat due to its impact on health and life. The enforcement of counterfeit medicines by the Pharmacy Enforcement Officers is surrounded by numerous issues and challenges. The aims of this study is to determine the issues and challenges facing the Pharmacy Enforcement Officers in the enforcement of counterfeit medicines and also to provide some recommendations which could improve the standard and quality of their enforcement exercise. The research is carried out using qualitative research method, library research on the primary sources of the laws and statutes in Malaysia, England and Wales as well as the fieldwork involving semistructured interviews in Malaysia. The legal chapters (chapter 3 and 4) provide the legal framework in the enforcement of the counterfeit medicines in Malaysia, England and Wales. The findings chapter (chapter 5), reports on the fieldwork findings of the two respondents regarding their perceptions on the issues and challenges facing the Pharmacy Enforcement Officers in the enforcement on counterfeit medicines in Malaysia. Issues identified are divided into law-related, socio-economic and operational-related. Challenges identified are divided into the detection of the counterfeit medicines, the challenges in the investigation process, the challenges in the prosecution process and the socio-economic challenges. It is learned in this study that the Pharmaceutical Services Division should adopt a holistic approaches to enhance the standard and quality of the Pharmacy Enforcement Officers. This includes enhancing the cooperation with the stakeholders, taking steps to review the laws and provides training. The Pharmacy Enforcement Division should upgrade the facilities and technology as well as paradigm shift and approaches in the enforcement of the law by the Pharmacy Enforcement Officers. The Pharmacy Enforcement Officers should be more pro active and creative in considering the use of other relevant provisions and the laws. All these may be a catalyst in improving the standard and quality of the Pharmacy Enforcement Officers in carrying out their enforcement tasks.